Acceleration-based joint stability parameters for total knee arthroplasty that correspond with patient-reported instability. (October 2013) - Roberts, Dustyn; Khan, Humera; Kim, Joo H; Slover, James; Walker, Peter S
There is no universally accepted definition of human joint stability, particularly in nonperiodic general activities of daily living. Instability has proven to be a difficult parameter to define and quantify, since both spatial and temporal measures need to be considered to fully characterize joint stability. In this preliminary study, acceleration-based parameters were proposed to characterize the joint stability. Several time-statistical parameters of acceleration and jerk were defined as potential stability measures, since anomalous acceleration or jerk could be a symptom of poor control or stability. An inertial measurement unit attached at the level of the tibial tubercle of controls and patients following total knee arthroplasty was used to determine linear acceleration of the knee joint during several activities of daily living. The resulting accelerations and jerks were compared with patient-reported instability as determined through a standard questionnaire. Several parameters based on accelerations and jerks in the anterior/posterior direction during the step-up/step-down activity were significantly different between patients and controls and correlated with patient reports of instability in that activity. The range of the positive to negative peak acceleration and infinity norm of acceleration, in the anterior/posterior direction during the step-up/step-down activity, proved to be the best indicators of instability. As time derivatives of displacement, these acceleration-based parameters represent spatial and temporal information and are an important step forward in developing a definition and objective quantification of human joint stability that can complement the subjective patient report.